Suppressing Electrode Crosstalk and Prolonging Cycle Life in High‐Voltage Li Ion Batteries: Pivotal Role of Fluorophosphates in Electrolytes. Issue 13 (31st May 2022) - Klein, Sven; Haneke, Lukas; Harte, Patrick; Stolz, Lukas; van Wickeren, Stefan; Borzutzki, Kristina; Nowak, Sascha; Winter, Martin; Placke, Tobias; Kasnatscheew, Johannes
Abstract: High‐voltage Li ion batteries are compromised by lower cycle life due to enhanced degradation of cathode material, for example LiNi0.5 Co0.2 Mn0.3 O2 (NCM523). Crucial part is the initiated electrode crosstalk, that is transition metal (TM) dissolution from the cathode and subsequent deposition on the anode, as it forces formation of high surface area lithium, capacity losses and risk of Li dendrite penetration, finally leading to an abrupt end‐of‐life (=rollover failure). Hence, suppression of this failure cascade is the pivotal strategy to prolong cycle life. A pragmatic approach was presented: the electrolyte manipulation towards formation/presence of fluorophosphates, as they effectively suppressed electrode crosstalk through TM scavenging. Either, they could be intrinsically formed, e. g. by elimination of ethylene carbonate (EC) solvent (=EC‐free electrolyte), or simply externally added, e. g . using (good‐soluble) lithium difluorophosphate electrolyte additive. Their effectiveness was demonstrated for conventional EC‐based and EC‐free electrolytes at limiting conditions (4.5 and 4.6 V, respectively). In parallel to supportive approach combinations (e. g. coating), also destructive combinations were highlighted, that is approaches, which even decrease the fluorophosphate content, e. g. vinylene carbonate additive in EC‐free electrolytes. Finally, by demonstrating the value of (concentration‐optimized) fluorophosphates, appropriate benchmark electrolyte formulations for high‐voltage LIBs were discussed. Abstract : Enhancing cell voltage in Li ion batteries : a pragmatic strategy to enhance energy density, however, compromised by decreased cycle life, frequently resulting in rollover failure. Dissolution of transition metals (TMs) from cathode and deposition on anode (= electrode crosstalk) triggers an inhomogeneous Li plating (e. g. Li dendrites), thus capacity losses and even short‐circuits. Fluorophosphates (Li x PO y F z ) could scavenge TMs and enhance cycle life, though, its concentration was crucial for performance and sensitively depended on applied cell materials.